Buckling of stainless steel welded I-section columns - Tuezney, S; Lauwens, K; Afshan, S; Rossi, B (Elsevier, 2021)
This paper studies the buckling behaviour and design of welded I-section stainless steel columns. Experimental and numerical structural performance data together with the design methods for stainless steel welded I-section columns available in the literature have been collated and reviewed. A numerical modelling programme including validation and parametric studies has been carried out to supplement the literature experimental and numerical data for the assessment of the existing codified and literature proposed flexural buckling design formulations for stainless steel welded I-section columns. Columns of austenitic, duplex and ferritic stainless steel grades undergoing major axis and minor axis flexural buckling have been investigated. From comparisons with the EN 1993–1-4 (EC3) flexural buckling capacity predictions, it was found that (1) for the austenitic welded I-section columns, the EC3 buckling curve (α = 0.76 and λ¯0 = 0.2) is suitable for both axes, (2) for the duplex and ferritic grades, the EC3 buckling curve (α = 0.76 and λ¯0 = 0.2) is conservative, and a higher buckling curve with (i) α = 0.49 and λ¯0 = 0.2 for both axes or (ii) α = 0.49 and λ¯0 = 0.2 for minor axis and α = 0.34 and λ¯0 = 0.2 for major axis may be adopted. In addition, comparisons with the recently proposed Continuous Strength Method showed marginally improved strength predictions but with slightly higher scatter.